2012
DOI: 10.1038/oby.2011.400
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibrillin‐3 and Transcription Factor‐7‐Like 2 Gene Variants With Metabolic Phenotypes in PCOS

Abstract: Polycystic ovary syndrome (PCOS) is a complex genetic disease characterized by heritable reproductive and metabolic abnormalities. Genetic variants associated with the reproductive phenotype have been mapped to the fibrillin-3 (FBN3) gene and to a novel transcription factor-7-like 2 (TCF7L2) locus (rs11196236 G). The association of these genetic variants with metabolic phenotypes was investigated in 31 PCOS and 18 control women of European ancestry. The insulinogenic index during an oral glucose tolerance test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…In PCOS women with abnormal glucose tolerance, TCF7L2 polymorphisms were associated with defects in insulin secretion (32). Another study with a small sample of 31 PCOS women has found that SNP rs11196236 was associated with peripheral insulin (15). By contrast, similar to other studies with PCOS populations (14, 33, 34), we did not find an association between insulin resistance and SNPs of the TCF7L2.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In PCOS women with abnormal glucose tolerance, TCF7L2 polymorphisms were associated with defects in insulin secretion (32). Another study with a small sample of 31 PCOS women has found that SNP rs11196236 was associated with peripheral insulin (15). By contrast, similar to other studies with PCOS populations (14, 33, 34), we did not find an association between insulin resistance and SNPs of the TCF7L2.…”
Section: Discussioncontrasting
confidence: 56%
“…Association studies on the single nucleotide polymorphisms (SNPs) of the TCF7L2 gene in PCOS women have produced controversial data, with some studies showing association between SNPs rs7903146 and rs11196236 with obesity-related traits (14) and peripheral insulin resistance (15) and others reporting no such association (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…As TGF-β signaling is currently implicated in the pathogenesis of PCOS in women by genetic epidemiologic evidence (Jones et al, 2007; Raja-Khan et al, 2010; Urbanek et al, 1999, 2007), our EPA monkey data support the potential contributory role of epigenomic perturbation in the etiology of PCOS. In support of this, since a reliable genetic marker for PCOS may be fibrillin-3 (Yalamanchi et al, 2012), a key TGF-β-related signaling element expressed in the human fetal ovary (Hatzirodos et al, 2010) when fetal T exposure most comprehensively induces PCOS-like traits in EPA female monkeys, EPA monkeys may epigenetically mimic PCOS in women. Given dysfunctional TGF-β signaling as a putative genetically-based mechanism for developing PCOS, our findings of altered methylation of TGFβ3, TGFBR1, KRAS, BMP2, TFE3, Runx3 and Hoxc8, complement previous studies implicating TGF-β superfamily members or their regulators in the pathophysiology of PCOS, including AMH, inhibin B, growth differentiation factor 9, activin A, follistatin, and fibrillin-3 (Xu et al, 2011).…”
Section: Molecular Epigenetic Signature Of Fetal T Exposure In Femmentioning
confidence: 99%
“…Neuroglycopenic symptoms were assessed every 15 min as reported [10]. Arterialized venous blood samples were obtained as reported [15] at −30, −15, and 0-min and every 5-min for the duration of the study. Blood glucose levels were determined in every sample using a YSI Glucose Analyzer (YSI Inc, Yellow Springs, OH).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose, [6,6 2 H]-glucose specific activity, total and bioavailable T, sex hormone binding globulin, dehydroepiandrosterone sulfate, insulin, C-peptide, epinephrine, and norepinephrine levels were determined as reported [15, 16]. Cortisol and GH assays were performed at the University of Virginia Center for Research in Reproduction Ligand Assay and Analysis Core on Siemens Immulite 2000 immunoassay system (Siemens Healthcare Diagnostics, LA, CA).…”
Section: Methodsmentioning
confidence: 99%